The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/dme.12367
|View full text |Cite
|
Sign up to set email alerts
|

The association between postprandial urinary C‐peptide creatinine ratio and the treatment response to liraglutide: a multi‐centre observational study

Abstract: Postprandial urinary C-peptide creatinine ratios before and during liraglutide treatment were weakly associated with the glycaemic response to treatment. Low pretreatment urinary C-peptide creatinine ratio may be more useful than higher values by predicting poorer glycaemic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
(31 reference statements)
1
28
0
1
Order By: Relevance
“…13 Our findings might suggest that the therapeutic response to liraglutide may be influenced by background β-cell function, for which background diabetes treatment and duration of diabetes may act as surrogate markers. Consistent with this view, studies have shown that higher C-peptide secretion is predictive of a larger treatment response to liraglutide, 12,14 or a greater likelihood of success when switching patients to liraglutide from insulin. 15,16 The mean reduction in HbA1c with liraglutide was smaller for patients treated with insulin, relative to patients receiving other therapies, but nevertheless remained clinically significant.…”
Section: Discussionmentioning
confidence: 76%
“…13 Our findings might suggest that the therapeutic response to liraglutide may be influenced by background β-cell function, for which background diabetes treatment and duration of diabetes may act as surrogate markers. Consistent with this view, studies have shown that higher C-peptide secretion is predictive of a larger treatment response to liraglutide, 12,14 or a greater likelihood of success when switching patients to liraglutide from insulin. 15,16 The mean reduction in HbA1c with liraglutide was smaller for patients treated with insulin, relative to patients receiving other therapies, but nevertheless remained clinically significant.…”
Section: Discussionmentioning
confidence: 76%
“…The majority of the studies assessed the clinical effectiveness of liraglutide without an active comparator (81.4%; N  = 35) [28, 29, 31, 34, 3639, 41–49, 5155, 57, 6064, 66–71]. Real-world studies with comparators were less frequently observed (18.6%; N  = 8); the most common comparators for liraglutide were: sitagliptin or any DPP-4i ( N  = 6) [32, 33, 35, 40, 56, 58], exenatide ( N  = 3) [33, 35, 50], glimepiride or any other SUs ( N  = 2) [30, 35], pioglitazone or other TZDs ( N  = 1) [35], and MET ( N  = 1) [35]; note: these numbers do not add up because some studies had more than one comparator.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently observed follow-up duration from these publications was ≥12 months (46.5%; N  = 20) [2847], followed by 6–12 months (34.9%; N  = 15) [4862], and <6 months (18.6%; N  = 8) [6370]. Real-world studies frequently reported data on the effect of liraglutide from outpatient settings (30.2%; N  = 13) [34, 39, 40, 42–44, 49, 55, 58, 60, 61, 66, 67]. The geographical scope of the review included studies from Europe ( N  = 24), the USA ( N  = 5), and Asia–Pacific ( N  = 14; see supplementary file 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations